2006
DOI: 10.1258/135763306776084365
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology reduces the number of patient referrals to a dermatologist

Abstract: During a two-year study, 505 teledermatology consultations were carried out on 503 patients of 29 participating general practitioners (GPs) in the province of Friesland. One overview and two detail digital photographs of the skin problems were taken on a digital camera and attached to an email message containing standard clinical information. These email messages were sent to a dermatologist, who replied by email after evaluation. After a median follow-up time of 548 days, the GPs were interviewed about the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…The percentage of visits avoided ranged from 12.8% to 72%. 10,15,17,32,63,65,68,71 The study that reported 12.8% clinic dermatology visits avoided also reported that 33.1% required clinic dermatology surgery. 15 Conclusions.…”
Section: Question 3: Clinical Outcomesmentioning
confidence: 99%
“…The percentage of visits avoided ranged from 12.8% to 72%. 10,15,17,32,63,65,68,71 The study that reported 12.8% clinic dermatology visits avoided also reported that 33.1% required clinic dermatology surgery. 15 Conclusions.…”
Section: Question 3: Clinical Outcomesmentioning
confidence: 99%
“…Process changes were defined as smallscale changes to some aspect of the individual referral process that did not involve the movement of staff or relocation of clinics, the methods in which referrals were triaged at hospital, or financial arrangements for referral. Process change interventions included: designated appointment slots and fast-track clinics for primary care referrals (n = 6), [60][61][62][63][64][65] direct access to screening (n = 9), 66 to referral (individual contact between a specialist and GP) (n = 11), [75][76][77][78][79][80][81][82][83][84][85] electronic referral systems (n = 10), [86][87][88][89][90][91][92][93][94][95] decision support tools (n = 10), [96][97][98][99][100][101][102][103][104][105] and waiting list review or watchful waiting (n = 3). [106][107][108] The overall picture for interventions that aim to moderate referral outcomes by changing an element of the referral process is mixed.…”
Section: Box 1 Main Search Strategymentioning
confidence: 99%
“…In our study, we found a marked reduction in these outpatient visits. Therefore, a distinct reduction in transport costs for the patients was achieved, an advantage of teledermatology 12 over the usual treatment modalities.…”
Section: Commentmentioning
confidence: 99%